Idiopathic Gingival Hyperplasia: A Case Report with a 17-Year Followup - Bien Lai; Joseph Muenzer; Michael W. Roberts (Case Reports in Dentistry)
This is a case report of a patient with idiopathic gingival hyperplasia and an undiagnosed genetic disorder that demonstrated static encephalopathy, mental retardation, developmental delay, seizures, hypotonia, and severe gingival hypertrophy. The clinical dental management and attempts to obtain a genetic diagnosis are described.